2018
DOI: 10.1186/s12870-018-1466-3
|View full text |Cite|
|
Sign up to set email alerts
|

A Glycine soja group S2 bZIP transcription factor GsbZIP67 conferred bicarbonate alkaline tolerance in Medicago sativa

Abstract: BackgroundEven though bicarbonate alkaline stress is a serious threat to crop growth and yields, it attracts much fewer researches than high salinity stress. The basic leucine zipper (bZIP) transcription factors have been well demonstrated to function in diverse abiotic stresses; however, their biological role in alkaline tolerance still remains elusive. In this study, we functionally characterized a bZIP gene from Glycine soja GsbZIP67 in bicarbonate alkaline stress responses.ResultsGsbZIP67 was initially ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 44 publications
1
15
0
Order By: Relevance
“…In wheat, TabZIP15 promotes the combination of ABF/AREB and ABRE (ABA response element) cis-acting elements through the expression of ABF/AREB to induce downstream target gene expression responding to plant salt and drought stress [ 34 ]. Similar results were observed for the GsbZIP67 gene in Alfalfa ( Medicago sativa ), overexpression of GsbZIP67 promoted the growth of plant roots and shoots and changed the physiological indicators of transgenic plants under bicarbonate salt-alkali stress [ 32 ].…”
Section: Introductionsupporting
confidence: 59%
“…In wheat, TabZIP15 promotes the combination of ABF/AREB and ABRE (ABA response element) cis-acting elements through the expression of ABF/AREB to induce downstream target gene expression responding to plant salt and drought stress [ 34 ]. Similar results were observed for the GsbZIP67 gene in Alfalfa ( Medicago sativa ), overexpression of GsbZIP67 promoted the growth of plant roots and shoots and changed the physiological indicators of transgenic plants under bicarbonate salt-alkali stress [ 32 ].…”
Section: Introductionsupporting
confidence: 59%
“…Recent studies have shown that bZIPs participate in bZIP transcriptional activation under bicarbonate-alkali stress and alter stress-related physiological indicators (such as reducing the accumulation of MDA and increasing both the activity of POD and the content of chlorophyll) and gene expression (excess GsbZIP67 expression in alfalfa) to improve salt-alkali tolerance (Wu et al, 2018). Members of the bZIP transcription factor family have been identified in a variety of higher plants.…”
Section: Induction Of Transcription Factor Expressionmentioning
confidence: 99%
“…Previous studies have reported that bZIP TFs were localized in nuclear [ 17 ], cytoplasmic [ 18 ], and endoplasmic reticulum [ 19 ]. Hence, to explore the subcellular localization of ChbZIP1 in plant cells, a ChbZIP1 sequence without the stop codon was constructed with the vector of pPZP211-GFP and transformed into Arabidopsis protoplasts.…”
Section: Resultsmentioning
confidence: 99%
“…Studies reported that bZIP TF could improve the survival of crop plants in alkaline conditions. A bZIP TF GsbZIP67, which was isolated from Glycine soja, overexpressed in alfalfa promoted plant growth under bicarbonate alkaline stress, as evidenced by longer roots and shoots [ 17 ]. DuanMu et al also found that the bZIP TFs family was significantly induced in the alkaline stress responses of wild soybean roots through transcriptome analysis [ 25 ].…”
Section: Discussionmentioning
confidence: 99%